Unsaturated and Saturated Permeabilities of Fiber Reinforcement: Critics and Suggestions - Park, Chung Hae; Krawczak, Patricia (Frontiers in Materials, 2015)
In general, permeability measurement results show a strong scattering according to the measurement method, the type of test fluid and the fluid injection condition, even though permeability is regarded as a unique property of porous medium. In particular, the discrepancy between the unsaturated and saturated permeabilities for the same fabric has been widely reported. In the literature, relative permeability has been adopted to model the unsaturated flow. This approach has some limits in the modeling of double-scale porosity medium. We address this issue of permeability measurement by rigorously examining the mass conservation condition. Finally, we identify that the pressure gradient is non-linear with positive curvature in the unsaturated flow and a misinterpretation of pressure gradient is the main reason for the difference between the saturated and unsaturated permeabilities of the same fiber reinforcement. We propose to use a fixed value of permeability and to modify the mass conservation equation if there are air voids which are entrapped inside the fiber tow. Finally, we also suggest some guidelines and future perspectives to obtain more consistent permeability measurement results.